Osteopathic and chiropractic techniques for the foot and ankle : clinical understanding and advanced treatment applications and rehabilitation for manual therapists /: clinical understanding and advanced treatment applications and rehabilitation for manual therapists. (2023) - Gyer, Giles; Michael, Jimmy; Kunasingam, Kumar; Inklebarger, James; Barrowman, Iain
No abstract available